MODEL KETERAMPILAN KECERDASAN EMOSIONAL (EQ) DALAM MENINGKATKAN PRESTASI BELAJAR SISWA - Hidayat, Hidayat (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2011)
Learning process at school is a complex process and comprehensive. Many people said that someone has to have high Intelligence Quotient (IQ) in order to gain high achievement since intelligence is potential asset which is making easier to study and produce optimum high learning achievement. As a matter of fact, in studying and learning process at school, some of the students cannot attain learning achievement equivalent with the Intelligence Quotient.  There are some students with high Intelligence Quotient but the learning achievements are low. In the other hand, there are some students with low Intelligence Quotient can attain high learning achievement. Therefore, Intelligence Quotient is not the only factor which is deciding someone’s success. Another factor which influences someone’s success is Emotional Intelligence (EI). Emotional Intellegence is someone’s ability to manage his/her emotional life with intelligence, keep the appropriateness of emotion and its expression through self-consciousness’ skill, self-control, self-motivation, emphatic, and social skill. Keywords: learning achievement, emotional Intelligence, self-control